2015
DOI: 10.1093/toxsci/kfv068
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Toxicity of Cadmium Telluride Quantum Dot Nanoparticles in Mammalian Hepatocytes

Abstract: There are an increasing number of studies indicating that mitochondria are relevant targets in nanomaterial-induced toxicity. However, the underlying mechanisms by which nanoparticles (NPs) interact with these organelles and affect their functions are unknown. The aim of this study was to investigate the effects of cadmium telluride quantum dot (CdTe-QD) NPs on mitochondria in human hepatocellular carcinoma HepG2 cells. CdTe-QD treatment resulted in the enlargement of mitochondria as examined with transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 71 publications
7
62
1
Order By: Relevance
“…Initial treatment with 20–500 µM of P2 (highest peroxyl radical scavenging activity) showed that 50 and 100 µM were optimum concentrations and both were used for all peptides. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, as described in an earlier research, was used for cytotoxicity and cytoprotective tests [15]. For both assays, HepG2 cells plated at 2 × 10 4 cells/well in 96-well tissue culture plates were grown for 24 h, washed with phosphate buffer saline solution (PBS, pH 7.2) followed by 24 h incubation with peptides and another wash, 200 µL of media were then added to cells intended for cytotoxicity and 200 µL of media containing 20 mM of AAPH to those used for cytoprotection evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Initial treatment with 20–500 µM of P2 (highest peroxyl radical scavenging activity) showed that 50 and 100 µM were optimum concentrations and both were used for all peptides. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, as described in an earlier research, was used for cytotoxicity and cytoprotective tests [15]. For both assays, HepG2 cells plated at 2 × 10 4 cells/well in 96-well tissue culture plates were grown for 24 h, washed with phosphate buffer saline solution (PBS, pH 7.2) followed by 24 h incubation with peptides and another wash, 200 µL of media were then added to cells intended for cytotoxicity and 200 µL of media containing 20 mM of AAPH to those used for cytoprotection evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated levels of Ca 2+ impaired mitochondrial membrane permeability, leading to the release of cytochrome c and induced apoptosis (Paesano et al, ; Richter et al, ). Some researchers have described that QDs could cause elevated intracellular Ca 2+ levels in HepG2 cells (Lu et al, ; Nguyen et al, ; Paesano et al, ). The Nguyen et al study showed that CdTe QDs led to a 7.4‐fold increase in Ca 2+ levels and was mediated via ROS.…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
“…The Nguyen et al study showed that CdTe QDs led to a 7.4‐fold increase in Ca 2+ levels and was mediated via ROS. Meanwhile high levels of Ca 2+ concentrations further increased ROS and aggravated oxidative stress (Nguyen et al, ). Similarly, CdSe/ZnS QDs caused an increase in the Ca 2+ concentration in L02 cells, which resulted in increasing mitochondrial ROS generation and activated NLRP3 inflammasomes (Lu et al, ).…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
“…56 While they may be useful tools for molecular biology as imaging agents, the toxicity of their components (i.e., cadmium and tellurium) is an issue. 74 This will likely limit the translation of quantum dots to in-human clinical applications in the near future. Non-toxic quantum dots are currently under research in a developmental stage.…”
Section: Different Classes Of Nanoparticles For Systemic Delivery mentioning
confidence: 99%